The fronto-parietal network and top-down modulation of perceptual grouping. - Han, S; Humphreys, G (2007)
We examined the role of the fronto-parietal cortex in top-down modulation of perceptual grouping by proximity, collinearity, and similarity, by recording event related brain potentials from two patients with fronto-parietal lesions and eight controls. We found that grouping by proximity and collinearity in the controls was indexed by short-latency activities over the medial occipital cortex and long-latency activities over the occipito-parietal areas. For the patients, however, both the short- and long-latency activities were eliminated or weakened. The results suggest that the fronto-parietal network is involved in facilitation of both the early and late grouping processes in the human brain.